EFFECTIVENESS OF PIANO VIRTUAL MEDIA ON THE PGSD STUDENTS RETENTION IN BASIC PIANO THEORY - Akmal, Rudi; Ginanjar, Ani Yanti; Shintawati, Euis (PrimaryEdu : Journal of Primary Education, 2020)
This study was conducted to determine the effectiveness of virtual piano media on PGSD students' memory on scale material. This study used a quasi-experimental one-group pretest-posttest design method. This study did not use a comparison class but already used a preliminary test so that the effectiveness of virtual piano media can be ascertained with certainty. In this study, the research subjects were first given a pretest to determine the extent of students' understanding before being given treatment using virtual piano media. The subjects in this study were 35 students. This research uses to test and non-test instruments. The non-test form includes distributing questionnaires. The data analysis technique used a parametric test for N-gain improvement and Paired Samples Test SPSS Version 25. The results proved that there was a significant difference between the pretest score and the posttest score after treatment with a 2-tailed sign value of 0.000 â‰¤ 0.05. Then there is a significant increase in the memory of students who use learning with virtual piano media rather than direct learning. It can be seen that learning with Virtual Piano Media provides a significant increase with an average N-gain of 0.72 and is included in the high category.